2013
DOI: 10.1248/bpb.b12-01067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrathecal Dexmedetomidine on Low-Dose Bupivacaine Spinal Anesthesia in Elderly Patients Undergoing Transurethral Prostatectomy

Abstract: Low-dose bupivacaine can limit the spinal block level with minimal hemodynamic effects and yield a rapid recovery, but sometimes it may not provide adequate anesthesia for surgery. Dexmedetomidine, a selective α2-adrenoreceptor agonist, was shown to be a potent antinociceptive agent when given intrathecally in animals and humans. The purpose of this study was to evaluate the adjuvant effects of intrathecal dexmedetomidine in elderly patients undergoing transurethral prostate surgery with low-dose bupivacaine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
78
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 37 publications
10
78
3
Order By: Relevance
“…It has an added advantage because, if the sensory block is achieved earlier at T6 dermatome, surgery can also be started earlier in group II as compared with group I. Previously it was also observed that time taken for regression of sensory block to S1 dermatome was delayed with the addition of dexmedetomidine to bupivacaine [12,[16][17][18] , which is in accordance with the present study. Complete motor blockade was achieved earlier and the duration of motor block was more prolonged in group II as compared with group I.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has an added advantage because, if the sensory block is achieved earlier at T6 dermatome, surgery can also be started earlier in group II as compared with group I. Previously it was also observed that time taken for regression of sensory block to S1 dermatome was delayed with the addition of dexmedetomidine to bupivacaine [12,[16][17][18] , which is in accordance with the present study. Complete motor blockade was achieved earlier and the duration of motor block was more prolonged in group II as compared with group I.…”
Section: Discussionsupporting
confidence: 90%
“…Addition of dexmedetomidine to intrathecal bupivacaine produced prolonged postoperative analgesia, and requirement of rescue analgesia in the postoperative period was also decreased [13,[16][17][18][19] . In the present study, no sedative was given during premedication, and thus most of the patients had sedation score in the range of 0 and 1 at all measured intervals in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…24 In other studies, it was observed that addition of various doses of clonidine to bupivacaine intrathecally significantly prolongs duration of analgesia of bupivacaine, 16,27,28 while others reported that addition of dexmedetomidine to bupivacaine significantly prolongs the duration sensory and motor block and post-operative analgesia. 23,25,[29][30][31] …”
Section: Discussionmentioning
confidence: 99%
“…Previous few other studies have described the intrathecal use of dexmedetomidine in a wide range (2-10 μg) [17][18][19][20].…”
mentioning
confidence: 99%